Tacrolimus in Solution as an Option to Inflammatory Conditions of the Scalp - Scharf, Camila; Licata, Gaetano; Briatico, Giulia; Pellerone, Sebastiano; Argenziano, Giuseppe; Giorgio, Caterina Mariarosaria (Dermatology Practical & Conceptual, 2023)
Introduction: Several dermatological diseases lead to inflammatory conditions of the scalp. Most of these afflictions are recalcitrant and require long term maintenance treatment.Objectives: We present a case series where topical tacrolimus was used in a solution vehicle for these conditions.Methods: A total of 22 patients (aged 24-90 years) with confirmed diagnosis of lichen planus pilaris (LPP),discoid lupus (DL),frontal fibrosing alopecia (FFA),erosive pustulosis of the scalp (EPS) or folliculitis decalvans (FD) were evaluated and treated with tacrolimus solution (0.1%) applied twice daily for 1 month, then once daily for another month and alternate days for 4 months. Efficacy was evaluated by an investigator global assessment,clinical and dermoscopic evaluation at weeks 4,8 and 24.The safety assessment included monitoring of all adverse events.Results: The study included 13 patients with LPP, 2 with DL, 2 with FD, 2 with EPS and 3 with AFF.After 1 month, 14 patients (63.6%) had a good response and 7 (31.8%) had excellent response.After 2 months, 16 patients (72.7%) had excellent response, and this response was persistent after 6 months of treatment.Conclusions: Tacrolimus in solution,even if not yet commercially available,was an effective and well tolerated alternative for the maintenance treatment of inflammatory conditions of the scalp.